(untitled) (Global Journal of Medical Research, 2018)
The aim of this study is to evaluate obstetric complications and perinatal outcomes in pregnant women with morbid obesity (BMI ≥ 40.0 kg/m²) compared to pregnant women with normal weight (BM I 18.5-24.9 kg/m²). It is a retrospective case-control study undertaken by the Department of Obstetrics at Hospital Universitario Doctor Peset, Valencia (Spain) between May 2008 and July 2016. A total of 50 patients were included in each study group. Morbidly obese pregnant patients had a higher rate of nulliparity (P = 0.03), chronic hypertension (P = 0.008), preeclampsia (P = 0.03), gestational diabetes (P = 0.013) and delivery by caesarean section (P = 0.04) compared to control patients with normal weight. A closer monitoring of morbidly obese pregnant women is recommended to prevent, reduce and properly handle the complications that may arise during pregnancy, both for the mother and the fetus.